Study of Oligosacharida Content from Various Sweet Potatoes and Application as Fuctional Drink - Irma Susanti; Eddy Sapto Hartanto; Ning Ima Wardayanie (Balai Besar Industri Agro, 2012)
In order to support food diversification, the effort to increase value-added sweet potatoes, which are very abundant in Indonesia, is necessary to conduct. Therefore, the research was conducted to study the content of oligosacharide from various cultivars of sweet potatoes, to develop formulation and to examine consumen acceptance of sweet potatoes drink. The steps of the research were consisted of production of sweet potatoes flour, extraction of oligosacharide, analysis of oligosacharide content, production of sweet potatoes drinks and its organoleptic test.Sweepotatoes flour were made by slicing the tuber, drying at 55 -60 C for plus minus 20 hours, grinding and shieving with mesh 80. The flour extraction was done usinng ethanol 70% for 15 hours and then evaporated using rotary evaporator. The oligosacharide content was analyzed by thin layer chromatography and HPLC. Sweet potatoes drink were produced as follow : size reduction, blanching, water addition with ration flour ti water of 1:2, filtering to separated the starch and formulation.The result showed that the highest oligosacharides content was white sweet potatoes with rafinose content 0,15%, 0,02% stachiose, dan 0,11% malthohexose, while the highest oligosacharide content of sweet potatoes drink was red sweet potatoes with 0,07% rafinose. Hedonic test showed that red sweet potatoes drink with 10% sugar and 0,1% citric acid was the most prefered with average score for taste, color were 3.50 and for flavor was 3.45.